Obesity as a predictor of falls among older women - Bhurtun, Hanish (2012)
In older people’s falls often lead to hospitalisation and lengthy recovery in health care institutions and this may be conducive to financial strain on health care systems. The propensity or risk of falling rises as the individual gets older and frailer. Fear of falling, previous history of falling, poor mobility, limitations in Activities of Daily Living (ADL), side effects of medications, hazardous environment, poor vision and hearing, poor postural balance and gaits impairment are among the frequent factors that give rise to falls amongst older people. However, studies focused on obesity as a risk factor for falls are rarer.